Synthesis and characterization of MgO nanostructures by different synthesis methods / Nor Fadilah Chayed - Chayed, Nor Fadilah (2014)
Magnesium oxide (MgO) is an interesting material and has unique properties which is applicable in many applications. In this research, novel MgO nanostructures o f ultra-thin sheets were synthesized using three different synthesis methods which are solid-state reaction, sol-gel and combustion methods. The synthesis condition was optimized to obtain pure MgO compound. These pure samples were characterized using Simultaneous Thermogravimetric Analyzer (STA), X-Ray Diffraction (XRD), High Resolution Transmission Electron Microscopy (HRTEM) and UV-Vis spectroscopy. The results shows pure MgO nanostructures can be obtained at the temperature of 600 °C for all synthesis methods that gives the ultra-thin nano sheets as can be seen from high resolution TEM. Different synthesis methods can give surprisingly the same morphology but in different thicknesses. However, combustion method gives the thinnest nanosheets followed by the sol gel and solid-state reaction methods. The band gap energy obtained for MgO samples synthesized by all methods have values of 5.825 eV to 5.955 eV which are much lower than the MgO bulk value of 7.8 eV. The characteristics of the band gap change with annealing time are different for the samples prepared by different preparation process. Therefore, the band gap energies o f MgO nanostructures are sensitive to the different synthesis methods. Results show that the band gap energies of nanostructures can be tuned to a suitable value needed for various applications by controlling the annealing time. Solgel method is the best method for producing MgO nanostructures at a temperature of 600 °C and at the shortest possible time of 1 h and also capable of producing large amounts of final product compared to the other methods.